Power Abuse in Child Sexual Abuse in Indonesia - Kanya Eka Santi (Indonesian Social Work Consortium (ISWC), 2024)
Child sexual abuse (CSA) in Indonesia is a critical issue shaped by the dynamics of power abuse. This study examines how perpetrators, often trusted figures such as family members, educators, or community leaders, exploit their authority to commit sexual abuse against children. Using a multiple case study approach, the research analyzes 15 cases from various regions in Indonesia. The findings reveal that CSA frequently involves the manipulation of power through threats, inducements, and the exploitation of cultural or religious norms. Contributing factors such as patriarchal norms, social stigma, and institutional weaknesses exacerbate the vulnerability of victims and hinder their access to justice. Framed within Michel Foucault’s theory, the power dynamics in these cases encompass hierarchies, normalization of violence, and discursive control. Perpetrators leverage their authority to instill fear and silence victims, while gaps in legal systems and patriarchal cultural values reinforce impunity. The long-term impact on victims includes psychological trauma, social stigma, and diminished quality of life. The study recommends strengthening child protection systems through public awareness campaigns, responsive reporting mechanisms, psychosocial support, and stricter oversight of educational and religious institutions to prevent and address CSA holistically.